2006
DOI: 10.1159/000094993
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Carotid Plaque Occurrence

Abstract: Background: Increased carotid intima media thickness (CIMT) is frequently associated with established modifiable and non-modifiable cardiovascular risk factors, and is thought to be an independent predictor of ischemic cerebrovascular and cardiac events. The presence of carotid plaque is considered an established feature of atherosclerosis. There exist few longitudinal data on the predictive role of CIMT in the occurrence of carotid plaque. Methods: We restudied the survivors of a cohort of the San Daniele Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…Several studies conducted in predominantly Caucasian populations reported cross-sectional associations between cIMT and plaque [31-33]. In addition, five longitudinal studies, with time spans from four to twelve years, have shown positive associations between cIMT, particularly in the CCA, with the development of carotid plaque [24, 30, 34-36]. Our findings regarding CCA cIMT in relation to incident plaque are not inconsistent with the latter studies.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Several studies conducted in predominantly Caucasian populations reported cross-sectional associations between cIMT and plaque [31-33]. In addition, five longitudinal studies, with time spans from four to twelve years, have shown positive associations between cIMT, particularly in the CCA, with the development of carotid plaque [24, 30, 34-36]. Our findings regarding CCA cIMT in relation to incident plaque are not inconsistent with the latter studies.…”
Section: Discussionsupporting
confidence: 59%
“…Our findings regarding CCA cIMT in relation to incident plaque are not inconsistent with the latter studies. However, differences in study design, including longer follow up in other studies [34, 35], categorization of cIMT [24, 30, 34] rather than a continuous examination, as well as differences in study sample characteristics and size may explain variability in findings. The other longitudinal studies did not examine lateral-specific ICA and bif cIMT in relation to incident plaque like we did.…”
Section: Discussionmentioning
confidence: 99%
“…Gnasso et al [50] showed that CIMT was strongly and significantly associated with the presence of plaques and/or stenosis in the carotid arteries after adjustment for coronary heart disease risk factors. The Aging Vascular Study [51], the Tromsø Study [52], the San Daniele Project [53] and a study of health in Pomerania [54] also confirmed that CIMT independently predicts incident carotid plaque formation in a prospective manner.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have suggested that an increased intima media thickness of the common carotid artery is a good predictor of atherosclerotic plaques occurrence [5,6,7]. In turn, the presence of carotid plaques is a powerful indicator of future ischemic events [8,9].…”
Section: Introductionmentioning
confidence: 99%